Revitalizing rural areas by boosting educational advancement through social capital integration - Marole Nkosikhona Moloi; Sibongamandla Silindokuhle Dlomo (International Journal of Educational Management and Development Studies)
Community development in rural areas is crucial for enhancing educational quality by addressing the diverse needs of students, families, and the broader community. This study investigates how leveraging social capital can significantly improve educational outcomes in rural communities. The primary objective of this study is to explore how community development initiatives, underpinned by social capital, contribute to educational advancements by integrating essential services such as healthcare, social welfare, after-school programs, and parental involvement directly within the educational framework. The study employs a systematic review methodology guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. This approach involves a comprehensive literature review to identify and analyze relevant studies. PRISMA guidelines were followed to ensure a rigorous and transparent reporting process, enhancing the reliability and validity of the findings in this study. The findings reveal the transformative impact of social capital on educational quality. Initiatives that effectively mobilize social networks and relationships lead to improved academic performance, social development, and emotional well-being of students. The study reveals the significance of stakeholder collaboration, supportive policies, and innovative pedagogies in sustaining and scaling these community-driven efforts. It is recommended by this study to strengthen stakeholder engagement, advocate for supportive policies, and integrate innovative teaching methods that will sustain and expand educational advancements. This study offers valuable insights into how social capital can address educational disparities and promote sustainable development in rural communities.